2022
DOI: 10.1002/ece3.8732
|View full text |Cite
|
Sign up to set email alerts
|

Host and geographic barriers shape the competition, coexistence, and extinction patterns of influenza A (H1N1) viruses

Abstract: The influenza virus mutates and spreads rapidly, making it suitable for studying evolutionary and ecological processes. The ecological factors and processes by which different lineages of influenza compete or coexist within hosts through time and across geographical space are poorly known. We hypothesized that competition would be stronger for influenza viruses infecting the same host compared to different hosts (the Host Barrier Hypothesis), and for those with a higher cross‐region transmission intensity (the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 86 publications
(161 reference statements)
0
6
0
5
Order By: Relevance
“…These processes are most evident in the 2015 viruses, in which consistent phylogenetic grouping following geographic patterns is observed ( Figures 1 – 4 , Figures S1 – S3 ) and noticed as well in the relationship of M and NS genes from virus A/swine/Antioquia/0201/2009 with classic viruses encountered in the same region ( Figure S3 , Figures 4 , 5 ). Multiple studies with the H1N1 subtype reported variations among regions, where evidence of separate evolution could eventually generate new clades and subclades ( 16 , 60 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These processes are most evident in the 2015 viruses, in which consistent phylogenetic grouping following geographic patterns is observed ( Figures 1 – 4 , Figures S1 – S3 ) and noticed as well in the relationship of M and NS genes from virus A/swine/Antioquia/0201/2009 with classic viruses encountered in the same region ( Figure S3 , Figures 4 , 5 ). Multiple studies with the H1N1 subtype reported variations among regions, where evidence of separate evolution could eventually generate new clades and subclades ( 16 , 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…H1N1pdm09 viruses were introduced in the Colombian territory in 2009 (34), and since then, a clear dominance has been obeyed by being the only subtype detected. This indicates the displacement of the classic subtype due to a competitive dynamic (16,55) in which H1N1pdm09 virus was more efficient in terms of higher viral fitness and antigenic difference after its recent installment (17,56,57). Such sustained superiority is contrary to what has been seen in other countries, where H1N1pdm09 circulates but not as the dominant subtype (15,58,59).…”
Section: Strain Name Isolation Region Isolation Source Global Swine H...mentioning
confidence: 99%
See 1 more Smart Citation
“…For Influenza A it has been shown that host and geographic barriers shape the competition, extinction, and coexistence patterns of H1N1 lineages and clades. [56] Also, like the Venezuelan equine encephalitis virus, a different and enzootic vector can be present in the Amazon or the interface between forest and agriculture [49,50]. It has been demonstrated that the genetic diversity of the West Nile virus depended on the mosquito species [57].…”
Section: Transmission By Vectorsmentioning
confidence: 99%
“…La influenza aviar, también conocida como gripe aviar es una de las enfermedades más comunes a nivel mundial; su importancia radica en las duras consecuencias que puede generar en la industria avícola por la muerta de los animales, que DOI: https://doi.org/10.22579/22484817.988 económicas (Kanaujia et al, 2022;Ravikumar et al, 2022); también al ser una enfermedad zoonótica (transmisión de animales a humanos), esta enfermedad puede cursar desde leves síntomas respiratorios hasta la muerte; lo anterior sumado a su alto potencial pandemiogeno, la convierte en una enfermedad de elevada importancia para la salud pública (Cheng et al, 2022;OMS, 2018;World Organisation for Animal Health, n.d.; Yago, 2016).…”
Section: Generalidades Y Antecedentes De La Influenza Aviarunclassified